2020
DOI: 10.3389/fendo.2020.592373
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Muscle–Liver Crosstalk to Treat Nonalcoholic Steatohepatitis

Abstract: Non-alcoholic fatty liver disease (NAFLD) has reached epidemic proportions, affecting an estimated one-quarter of the world’s adult population. Multiple organ systems have been implicated in the pathophysiology of NAFLD; however, the role of skeletal muscle has until recently been largely overlooked. A growing body of evidence places skeletal muscle—via its impact on insulin resistance and systemic inflammation—and the muscle-liver axis at the center of the NAFLD pathogenic cascade. Population-based studies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 161 publications
0
82
0
Order By: Relevance
“…40 A causal link cannot be inferred from the present analysis; however, it is tempting to speculate that a high-fat content contributes to NAFLD progression: peripheral insulin resistance and/or perturbation of the muscle metabolism and secretome associated with muscle fat 14,41,42 may promote liver inflammation and hepatocellular injury. 6,12,[14][15][16] Further studies in preclinical models, in which we showed that muscle fat infiltration (but not sarcopenia) was specifically associated with NASH, 43 will clarify the exact nature and directionality of the muscleliver axis in NAFLD progression and potentially unravel new relevant therapeutic targets.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…40 A causal link cannot be inferred from the present analysis; however, it is tempting to speculate that a high-fat content contributes to NAFLD progression: peripheral insulin resistance and/or perturbation of the muscle metabolism and secretome associated with muscle fat 14,41,42 may promote liver inflammation and hepatocellular injury. 6,12,[14][15][16] Further studies in preclinical models, in which we showed that muscle fat infiltration (but not sarcopenia) was specifically associated with NASH, 43 will clarify the exact nature and directionality of the muscleliver axis in NAFLD progression and potentially unravel new relevant therapeutic targets.…”
Section: Discussionmentioning
confidence: 80%
“…18 Thus, patients with obesity are more likely to be categorized as sarcopenic when applying weight or BMI-based muscle mass scaling, as used in the majority of sarcopenia studies in NAFLD. [7][8][9][10][11][12][13]15,16 Moreover, high BMI per se is a well-known risk factor for NAFLD. 1 Hence, to find a low relative muscle mass in patients with NAFLD is not a surprise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle has been recognized as a vital organ for whole body metabolism, since it is a primary site for glucose uptake and storage, and it is also a reservoir of amino acids stored as protein [60]. However, recent studies have shown that sarcopenia, the loss of muscle mass and function, is a novel risk factor for developing NASH and muscle, and via its impact on insulin resistance and systemic inflammation, can be of importance in NASH pathogenesis [61,62]. Not only low muscle mass, but also an adverse muscle composition comprising a high muscle fat infiltration (myosteatosis) is associated with the severity of NASH [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have underscored that sarcopenia (i.e., decreased muscle mass) or adverse muscle composition (i.e., low muscle volume and muscle fat infiltration or myosteatosis) may influence both NAFLD development and progression. [66][67][68] Although important methodological differences exist across published studies, not all patients with NAFLD exhibit muscle alterations and it is likely that this pathogenic factor be more relevant in particular populations, such as nonobese or lean NAFLD, as well as older patients in which sarcopenia is more frequent. 69 Activation of the innate immune system has been implicated in NAFLD progression.…”
Section: Differential Contribution Of Pathogenetic Pathwaysmentioning
confidence: 99%